Improved gesturing in left-hemispheric stroke by right inferior parietal theta burst stimulation - Pastore-Wapp, Manuela; Gyurkó, Dávid M.; Vanbellingen, Tim; Lehnick, Dirk; Cazzoli, Dario; Pflugshaupt, Tobias; Pflugi, Stefanie; Nyffeler, Thomas; Walther, Sebastian; Bohlhalter, Stephan (Frontiers in Neuroscience, 2022)
Objectives: Apraxia is a common syndrome of left hemispheric stroke. A parieto-premotor-prefrontal network has been associated with apraxia, in which the left inferior parietal lobe (IPL-L) plays a major role. We hypothesized that transcranial continuous theta burst stimulation (cTBS) over the right inferior parietal lobe (IPL-R) improves gesturing by reducing its inhibition on the contralateral IPL in left hemispheric stroke patients. It was assumed that this effect is independent of lesion volume and that transcallosal connectivity is predictive for gestural effect after stimulation. Material and Methods: Nineteen stroke patients were recruited. Lesion volume and fractional anisotropy of the corpus callosum were acquired with structural magnetic resonance imaging (MRI) and diffusion tensor imaging (DTI). Each patient had pseudorandomised sessions with sham or with stimulation over the IPL-R or over the right inferior frontal gyrus IFG-R. Gesturing was assessed in a double-blinded manner before and after each session. We tested the effects of stimulation on gesture performance using a linear mixed-effects model. Results: Pairwise treatment contrasts showed, that, compared to sham, the behavioral effect was higher after stimulation over IPL-R (12.08, 95% CI 6.04 – 18.13, p<.001). This treatment effect was approximately twice as high as the contrasts for IFG-R vs. sham (6.25, 95% CI -0.20 – 12.70, p=.058) and IPL-R vs. IFG-R vs. sham (5.83, 95% CI -0.49 – 12.15, p=.071). Furthermore, higher fractional anisotropy in the splenium (connecting the left and right IPL) were associated with higher behavioral effect. Relative lesion volume did not affect the changes after sham or stimulation over IPL-R or IFG-R. Conclusion: One single session of cTBS over the IPL-R improved gesturing after left hemispheric stroke. Denser microstructure in the corpus callosum correlated with favorable gestural response. We therefore propose the indirect transcallosal modulation of the IPL-L as a promising model of restoring interhemispheric balance, which may be useful in rehabilitation of apraxia.